Transforming Hospital Housekeeping: The Kayakalp Journey - Jawahar S.K. Pillai; Biswajeevan Sahoo; Mukunda Chandra Sahoo; Bijayini Behera; Renju Sussan Baby; Mariamma V. George; Jyotirmayee Rath; Chandramani Sahoo; Ashoka Mohapatra; Gaurav Chhabra; Binod Kumar Behera; Arvind Kumar Singh; et al. (Global Journal on Quality and Safety in Healthcare)
Introduction The Kayakalp guidelines for public healthcare facilities under the Swachh Bharat Abhiyan (Clean India Mission) focus on improving sanitation, cleanliness, and infection control at public hospitals in India. This study was conducted in a 960-bed tertiary-level teaching hospital in eastern India. Housekeeping has been a challenge in public institutions, with factors like overcrowding and resource constraints. Tobacco and betel nut chewing, spitting, poor sanitation practices, and open urination are major challenges in ensuring sanitation at the hospital. The research objective was to study the implementation of the Kayakalp guidelines for quality improvement in housekeeping services at the institution. Methods A pre- and post-interventional study was conducted using the Plan-Do-Check-Act (PDCA) quality tool. Plan phases included the gap assessment using the Kayakalp checklist with numerical scoring. Necessary interventions were done under three headings: structure, processes, and outcomes in the “Do” phase. The “Check” phase included monitoring of the activities followed by the “Act” phase, which included a review of the action plan. External experts nominated by the government conducted the final assessments and recommended it as one of the cleanest hospitals. Results A 360-degree improvement was observed in hospital services, with assessment score improvement from 73.68% to 95.0%. The institution received the first prize in 2020 and 2021 and runners-up Kayakalp National Award under category “B” (Institute of National Importance) Hospitals in 2019. Conclusion The implementation of Kayakalp guidelines of the Government of India proved to be efficient in the improvement of housekeeping and infection control practices in the institution.